Trends and volatility in exchange rate of Indian rupee against pound sterling in pre and post-recession period - Kaur, Mandeep and Dhaliwal, Navkiranjit K. (Man & Development)
The foreign exchange market is an important element of the financial market of any country. It is the market where exchange rated is determined. - Reproduced
Keywords: Exchange rate, Indian rupee, Pound sterling, Growth rate, Trends, Volatility, Pre-recession period, Post-recession period